PEMAHAMAN PENDERITA DIABETES MELITUS DALAM UPAYA MENCEGAH TERJADINYA KOMPLIKASI ULKUS DIABETIKOne of the priorities of Indonesia's health development is to extend life expectancy by reducing the number of degenerative diseases. Degenerative disease is a c - Iswadi, Iswadi (SCIENTIA JOURNAL, 2021)
One of the priorities of Indonesia's health development is to extend life expectancy by reducingthe number of degenerative diseases. Degenerative disease is a chronic chronic disease thataffects a person's quality of life and productivity, including diabetes mellitus. Diabetes mellitusis a disease that we often encounter in the community because of its high mortality rate, besidesthat this disease also has a high impact on complications for patients such as diabetic ulcers, sothat various efforts to prevent complications of diabetic ulcers must be understood by patients.The purpose of this study to obtain information on the understanding of people with diabetesmellitus in an effort to prevent complications of diabetic ulcers. Methods the study wasconducted using a qualitative approach that was presented descriptively, both primary data andsecondary data in one of the Puskesmas working areas in Jambi City in 2016. Primary data wasobtained through questionnaires to a sample of 33 respondents, while secondary data was byreviewing medical record documents of respondents' visits. The results of the study showed thatmost of the 19 respondents (57.6%) had a good understanding, and 14 respondents (42.4%) had apoor understanding of preventing complications of diabetic ulcers. From the results of the studyit can be understanding of people with diabetes mellitus in preventing complications of diabeticulcers is good, but the percentage is still low, because there are still several components ofefforts to prevent complications of diabetic ulcers that respondents do not understand.